Hepatic encephalopathy in cirrhosis: a disorder of glial-neuronal signalling - Butterworth, Roger F. (Henry Stewart Talks, 2013)
Classification of hepatic encephalopathy, Hepatic encephalopathy in cirrhosis, Transjugular intrahepatic portosystemic shunt (TIPS), Hepatic encephalopathy post-TIPS, Neuropathology of hepatic encephalopathy in chronic liver failure, Cirrhosis-related Parkinsonism, PET studies in cirrhosis, Neuroinflammation and hepatic encephalopathy in cirrhosis, Systemic inflammatory response syndrome (SIRS) in cirrhosis, Translocator protein and hepatic encephalopathy in cirrhosis, Modulatory site for neurosteroids, Prevention and treatment of hepatic encephalopathy in cirrhosis, Emerging new therapeutic approaches